Early Development of Larvae and Juvenile of Largemouth Bass (Micropterus salmoides) and Selective Experiment on Different Feed Ingredient - Yuwan LI; Haohui LIANG; Yao QIN; Huijie LU; Minwei HUANG; Yanping MA; Guoxia WANG (Guangdong nongye kexue)
【Objective】To gain a more comprehensive understanding of the early development and initial feeding behavior of larval and juvenile largemouth bass, providing a scientific basis for large-scale breeding and the development of initial feeding diet.【Method】Using microscopic observation, biological measurement, and tissue sectioning methods, the morphological characteristics of the developmental stages of largemouth bass were studied, and the changes in digestion, immunity, and antioxidant enzyme activity of largemouth bass were analyzed. At the same time, biological measurement methods were used to measure the body length and weight of largemouth bass fed with different feed materials at 12 dah, and their survival rates were recorded.【Result】According to the disappearance of yolk sac, appearance of anus, fins and black spots during embryonic development of largemouth bass, it can be divided into the newly hatched larvae stage, larvae stage and juvenile stage,with an initial feeding time of 5 dah. Before 15 dah, the body weight and total length of the largemouth bass larvae slowly increased, while after 15 dah, the larvae and juveniles rapidly increased. In 0-26 dah, there was a phenomenon of allometric growth in the upper jaw length, total length and body mass. The activities of trypsin, lipase, and amylase in largemouth bass can be detected at 0 dah, while the activity of pepsin was not detected at 0-15 dah. The activity of trypsin and lipase first decreased and then increased from 0 to 26 dah, while amylase significantly increased.The liver and intestines of the newly hatched largemouth bass larvae were observed, with a embryonic stomach at 7 dah and a diffuse pancreas at 4 dah. The volume of the stomach cavity of 13 dah juvenile fish increased, and a small number of solid clusters of gastric glands can be observed. The staining of liver cell clusters deepens. The intestine initially differentiated into foregut and hindgut, and the number of pancreatic islet cells increased at 17 dah. The liver, pancreas, stomach, and intestinal structures of juvenile fish at 21 dah were similar to those of adult fish, and their development was basically completed. AKP and LZM levels gradually increased at 0-4 dah. AKP of 5-10 dah and LZM of 4-15 dah gradually decreased, while the AKP and LZM at 11-26 dah and 16-26 dah significantly increased. CAT and GSH-Px showed an overall trend of first increasing, then decreasing, and then increasing again. At 15-26 dah, T-SOD activity was significantly lower than the other dahs, while MDA showed the opposite change. The final body length and survival rate of the brine shrimp nauplii group were significantly better than the fermented earthworm paste group, soycomil group, and Spirulina platensis powder group. The final body mass and specific growth rate of the brine shrimp nauplii group and the fermented earthworm paste group were significantly higher than Spirulina platensis powder group. There was no significant difference in the coefficient of fatness among the groups.【Conclusion】Largemouth bass is divided into three stages: the newly hatched larvae stage (0-4 dah), larval stage (5-15 dah), and juvenile stage (16- 26 dah). The activities of digestive enzymes, immune enzymes, and antioxidant enzymes in larval largemouth bass are unstable during the initial feeding stage (5-10 dah) and the early weaning stage (10-15 dah), requiring a nutritionally comprehensive diet. The activities of digestive enzymes, immune enzymes, and antioxidant enzymes in largemouth bass ranging from 15 to 26 dah gradually stabilize, which can quickly improve their predation, swimming, and immune abilities. In addition, fermented earthworm paste has attractive properties and the best feeding effect. It can be used as a raw material for feeding largemouth bass larvae for further development and utilization.